A decade of radiomics research: are images really data or just patterns in the noise? - Pinto dos Santos, Daniel; Dietzel, Matthias; Baessler, Bettina (European Radiology, 2020)
• Although radiomics is potentially a promising approach to analyze medical image data, many pitfalls need to be considered to avoid a reproducibility crisis. • There is a translation gap in radiomics research, with many studies being published but so far little to no translation into clinical practice. • Going forward, more studies with higher levels of evidence are needed, ideally also focusing on prospective studies with relevant clinical impact.
CRIS-Team Scopus Importer:2020-08-14